The comparison of insect biodiversity between over logged forest and virgin forest - Neo, Wie Xuan. (2011., 2011)
The project was conducted in Sungai Asap and Bakun located in Kapit district, Sarawak. The over logged forest was located in MPOB oil palm plantation at Sungai Asap. There are three strips conserved as biodiversity conservation area for biodiversity study. For Virgin forest located in Sungai Badeng, Bakun area was a forest that not yet being exploited by human. The first objective of the study was to compare the different of insect diversity between over logged forest and virgin forest. Second objective is to compare the abundance of insect species between over logged forest and virgin forest. The biodiversity of insect between virgin forest and over logged forest can be studied by collecting the specimen using three methods of sampling. Methods of sampling used were malaise traps, yellow pan trap, and pit fall trap. Sampling was conducted at strip one at MPOB Diversity strips and at virgin forest at Bakun Strip. The trap was set up in the strip with 4 points where each point has one malaise trap, four pit fall trap's and four yellow pan traps. Traps was left and recollected after 5 days. Sample was preserved in Ethanol 95% and brought back to UPM to identify using the reference, An Introduction to the Study of Insect by Borror DJ. The result was to be different as virgin forest content less divest of insect population while over logged forest should have higher divest but same abundance compared to virgin forest. The Diversity and abundance of insect are influence by the season variation, vegetative diversity and human disturbance. Due to this three factors, the diversity of insects in MPOB diversity Strip 1 are more diverse compared to the Bakun Strip but both strip have same abundance.
Project paper (B.Agric.Sc.) - Universiti Putra Malaysia, 2011.